Virus-Specific T Cells for the Immunocompromised Patient - Houghtelin, Amy; Bollard, Catherine M. (Frontiers in Immunology, 2017)
While progress has been made in the treatment of both hematologic cancers and solid tumors, chemorefractory or relapsed disease often portends a dismal prognosis, and salvage chemotherapy or radiation expose patients to intolerable toxicities and may not be effective. Hematopoietic stem cell transplant (HSCT) offers the promise of cure for many patients, and while mismatched, unrelated or haploidentical donors are increasingly available, the recipients are at higher risk of severe immunosuppression and immune dysregulation due to graft versus host disease (GVHD). Viral infections remain a primary cause of severe morbidity and mortality in this patient population. Again, many therapeutic options for viral disease are toxic, may be ineffective or generate resistance, or fail to convey long term protection. Adoptive cell therapy with virus-specific T cells (VSTs) is a targeted therapy that is efficacious and has minimal toxicity in immunocompromised patients with CMV and EBV infections in particular. Products have since been generated specific for multiple viral antigens (multi-VST), which are not only effective but confer protection in 70-90% of recipients when used as prophylaxis. Notably, these products can be generated from either virus-naïve or virus-experienced autologous or allogeneic sources, including partially matched HLA-matched third-party donors. Obstacles to effective VST treatment are donor availability and product generation time. Banking of third-party VST is an attractive way to overcome these constraints and provide products on an as-needed basis. Other developments include epitope discovery to broaden the number of viral antigens targets in a single product, the optimization of VST generation from naïve donor sources, and the modification of VSTs to enhance persistence and efficacy in vivo.